The American Accounting Association-Sponsored Statements of Standards for Corporate Financial Reports: A Perspective (Book). - Zeff, Stephen A.; Mead, George C. (The Accounting Review, 1965)
Reviews the book "The American Accounting Association-Sponsored Statements of Standards for Corporate Financial Reports: A Perspective," vol. 3, by Harvey T. Deinzer.